Transmission line reliability and security - Pansini, Anthony J. (Fairmont Press ; Distributed by Marcel Dekker, 2004)
Annotation Electric service has become a necessity, not only in the lives of individuals, but also in the operation of public services. Already military surveillance and protection has been extended to nuclear power installations and will probably be extended to large power generating facilities. This timely book tackles both the problems of reliability caused by the deregulation of electric utilities, and those of security created by the events of 9-11 in clear, precise terms. Drawing upon his extensive hands-on knowledge of power systems gained during many years as an engineer in the industry, Mr. Pansini offers practical, innovative solutions to address these issues - solutions based in the design, construction, maintenance and operation of transmission facilities. You'll gain a clearer understanding of the real effects of deregulation on the reliability of existing transmission systems, and benefit from an expert's view of what may be done to maintain or improve their reliability. Some phenomena occurring in electric theory are included, in non- or semitechnical terms, for the benefit of the non-engineer.
Keywords: Electric power transmission.; Electric power systems -- Security measures.; Electric circuits -- Reliability.; elektronické knihy; electronic books